MiR-199a-5p inhibits monocyte/macrophage differentiation by targeting the activin A type 1B receptor gene and finally reducing C/EBPα expression. Issue 6 (25th September 2014) - Lin, Hai-Shuang; Gong, Jia-Nan; Su, Rui; Chen, Ming-Tai; Song, Li; Shen, Chao; Wang, Fang; Ma, Yan-Ni; Zhao, Hua-Lu; Yu, Jia; Li, Wei-Wei; Huang, Li-Xia; et al.
Abstract : miR-199a-5p inhibits monocyte/macrophage differentiation via down-regulating ACVR1B, further reducing phosphorylation of Smad2/3, resulting in decreased expression of C/EBPα. Abstract: miRNAs are short, noncoding RNAs that regulate expression of target genes at post-transcriptional levels and function in many important cellular processes, including differentiation, proliferation, etc. In this study, we observed down-regulation of miR-199a-5p during monocyte/macrophage differentiation of HL-60 and THP-1 cells, as well as human CD34 + HSPCs. This down-regulation of miR-199a-5p resulted from the up-regulation of PU.1 that was demonstrated to regulate transcription of the miR-199a-2 gene negatively. Overexpression of miR-199a-5p by miR-199a-5p mimic transfection or lentivirus-mediated gene transfer significantly inhibited monocyte/macrophage differentiation of the cell lines or HSPCs. The mRNA encoding an ACVR1B was identified as a direct target of miR-199a-5p. Gradually increased ACVR1B expression level was detected during monocyte/macrophage differentiation of the leukemic cell lines and HSPCs, and knockdown of ACVR1B resulted in inhibition of monocyte/macrophage differentiation of HL-60 and THP-1 cells, which suggested that ACVR1B functions as a positive regulator of monocyte/macrophage differentiation. We demonstrated that miR-199a-5p overexpression or ACVR1B knockdown promoted proliferation of THP-1 cells through increasing phosphorylation of Rb. We also demonstrated that the down-regulation of ACVR1B reduced p-Smad2/3, which resulted in decreased expression of C/EBPα, a key regulator of monocyte/macrophage differentiation, and finally, inhibited monocyte/macrophage differentiation.